2006
DOI: 10.1366/000370206775382631
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Oil and Oleic Acid Concentrations in Individual Corn (Zea Mays L.) Kernels Using Near-Infrared Reflectance Hyperspectral Imaging and Multivariate Analysis

Abstract: Due to their heterogeneous structure and variability in form, individual corn (Zea mays L.) kernels present an optical challenge for nondestructive spectroscopic determination of their chemical composition. Increasing demand in agricultural science for knowledge of specific traits in kernels is driving the need to find high-throughput methods of examination. In this study macroscopic near-infrared (NIR) reflectance hyperspectral imaging was used to measure small sets of kernels in the spectroscopic range of 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 20 publications
(24 reference statements)
0
52
0
Order By: Relevance
“…This preprocessing method is known to reduce the scattering effects smoothing the noise of the signal. It has led to improvement in the results of several studies of single seed applications using NIRS because it removed differences due to sample positioning (Weinstock et al, 2006).…”
Section: Data Processing and Discrimination Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This preprocessing method is known to reduce the scattering effects smoothing the noise of the signal. It has led to improvement in the results of several studies of single seed applications using NIRS because it removed differences due to sample positioning (Weinstock et al, 2006).…”
Section: Data Processing and Discrimination Modelsmentioning
confidence: 99%
“…However, NIRS has been used in several applications for single seed analysis with notable success. Quantitative applications in single corn kernels are mainly targeting oil content (Cogdill et al, 2004;Janni et al, 2008;Jiang et al, 2007;Orman and Schumann, 1992;Spielbauer et al, 2009;Weinstock et al, 2006), protein levels (Spielbauer et al, 2009), moisture calibrations (Armstrong, 2006;Finney and Norris, 1978), and starch (Spielbauer et al, 2009). The predictive ability of those calibrations indicated that NIRS is a suitable technology for screening organic compounds in single corn kernels.…”
Section: Introductionmentioning
confidence: 99%
“…The reported reflection spectra extend deeper into the NIR range than the transmission spectra, usually reaching 1700 nm. 4,6,7,9,10 Reflection, however, interrogates only the surface region of the kernel and only the region struck by the NIR beam, while diffuse transmission examines most of the bulk of the kernel. Some of the reflection-based studies have partly compensated for this by tumbling or dropping the kernels during analysis so as to view a larger portion of the kernel.…”
Section: Introductionmentioning
confidence: 99%
“…With a combination of microscopy and spectroscopy, FTIR could be used to quantify the chemical composition of microscopic samples [38]. Both FTIR and NIR imaging techniques that provide spatially resolved chemical information have been applied in pharmaceutical [39,40] and food industry [41]. The imaging techniques are helpful for better understanding biomass structure.…”
mentioning
confidence: 99%